Histological Spectrum of Skin Diseases in Tertiary Care Center of Eastern Nepal - Pradhan, Manish; Rai, Anjan; Karki, Sunita; Khadka, Niraj; K.C. , Srijana (Journal of Nobel Medical College, 2025)
Background: Skin diseases are common in developing countries, with their patterns differing significantly across nations and even within various regions of the same country. Histological diagnosis serves as an essential tool for clinicians, guiding accurate patient management and enabling the selection of the most effective clinical interventions. Materials and Methods: This retrospective descriptive study was conducted at the Department of Dermatology, Nobel Medical College and Teaching Hospital, Biratnagar, Nepal, to evaluate the histological spectrum of skin diseases over one year (March 2022–February 2023) after approval of institutional review comitteeof Nobel Medical College and Teaching Hospital . A total of 200 skin biopsy samples were analyzed using hematoxylin and eosin staining, with special stains used as necessary. Results: The majority of patients were male (63.5%) with a mean age of 39.13 years. The most commonly used biopsy technique was punch biopsy (48%), and the lower limb was the most frequent biopsy site (36.5%). Non-neoplastic lesions were predominant (84.5%), with infectious dermatoses—primarily Hansen’s disease—being the most common (47.5%). Papulosquamous disorders, eczema, immunobullous diseases, and connective tissue disorders each accounted for 6.5–13% of non-neoplastic cases. Neoplastic conditions comprised 15.5% of cases, with basal cell carcinoma being the most frequent tumor. Conclusion: Non-neoplastic lesions, particularly infectious dermatoses such as Hansen’s disease, were predominant, accounting for the majority of cases. Other non-neoplastic conditions, including papulosquamous disorders, eczema, and immunobullous diseases, were less frequent but still significant. Neoplastic conditions, primarily basal cell carcinoma, comprised a smaller proportion of the total cases.